Starch biosynthesis contributes to the maintenance of photosynthesis and leaf growth under drought stress in maize. (22nd July 2020) - AbdElgawad, Hamada; Avramova, Viktoriya; Baggerman, Geert; Van Raemdonck, Geert; Valkenborg, Dirk; Van Ostade, Xaveer; Guisez, Yves; Prinsen, Els; Asard, Han; Van den Ende, Wim; Beemster, Gerrit T. S.
Abstract: To understand the growth response to drought, we performed a proteomics study in the leaf growth zone of maize ( Zea mays L.) seedlings and functionally characterized the role of starch biosynthesis in the regulation of growth, photosynthesis and antioxidant capacity, using the shrunken‐2 mutant ( sh2 ), defective in ADP‐glucose pyrophosphorylase. Drought altered the abundance of 284 proteins overrepresented for photosynthesis, amino acid, sugar and starch metabolism, and redox‐regulation. Changes in protein levels correlated with enzyme activities (increased ATP synthase, cysteine synthase, starch synthase, RuBisCo, peroxiredoxin, glutaredoxin, thioredoxin and decreased triosephosphate isomerase, ferredoxin, cellulose synthase activities, respectively) and metabolite concentrations (increased ATP, cysteine, glycine, serine, starch, proline and decreased cellulose levels). The sh2 mutant showed a reduced increase of starch levels under drought conditions, leading to soluble sugar starvation at the end of the night and correlating with an inhibition of leaf growth rates. Increased RuBisCo activity and pigment concentrations observed in WT, in response to drought, were lacking in the mutant, which suffered more oxidative damage and recovered more slowly after re‐watering. These results demonstrate that starch biosynthesis contributes to maintaining leaf growth under drought stress and facilitates enhanced carbon acquisition upon recovery. Abstract : In this study, we developed a high‐resolution, multi‐level map of integrated set of proteomic, metabolite and cellular growth data, comparing developmental stages along the growth zone of the growing maize leaf under well‐watered and drought conditions. Our data suggested a contribution of starch synthesis to the growth response to drought. Making use of the shrunken‐2 mutant, defective in starch synthesis, allowed us to functionally characterize the changes in starch and sugar metabolism induced by drought, which resulted in novel mechanistic understanding of the physiological adaptation to drought. Starch accumulation balances the levels of soluble sugars such as glucose during the day and provides steady energy source during the night and thus enables maintaining cell division in the meristem. We demonstrate a correlation between functional starch biosynthesis and CO2 assimilation, which is important in the context of leaf growth under drought stress and recovery upon re‐watering.